EFFECT OF EDUCATION ON KNOWLEDGE, ADHERENCE, AND INTRAOCULAR PRESSURE ON GLAUCOMA OUTPATIENTS: A SYSTEMATIC REVIEW - Wahyuni; Yosi Irawati Wibowo; Adji Prayitno Setiadi (Universitas Airlangga, 2023)
Introduction: To evaluate educational interventions to improve patient knowledge, and adherence to glaucoma treatment that results in a reduction in intraocular pressure based on current clinical evidence. Methods: A systematic review of PubMed (NIH) was conducted to identify studies evaluating educational interventions to improve patient knowledge, and adherence to glaucoma treatment that resulted in decreased intraocular pressure. The search was conducted from March to August 2020. Results: The educational intervention was successful in increasing the skill of using eye drops for one month from 6% to 35%, and 64% after six months of education. The percentage of patients who successfully implanted the eye drops correctly increased from 66.7% to 82.2%. The educational intervention was successful in increasing adherence to treatment followed by MEMS from 67% -98% to 78% -86%. The adherence monitored with the pharmacy database resulted in a PDC of 57%, and the medication possession ratio (MPR) of 71% because many data were not recorded in the pharmacy. African American patients had significantly low adherence (OR = 0.29 95% CI = 0.16, 0.52). The educational intervention has no significant effect on the IOP value. Patients with low adherence tend to have low VFQ-25 (visual acuity) scores. After education, 99% of the patients were satisfied with the health program implemented. Conclusion: All educational interventions were successful in increasing patient knowledge, medication adherence, and eye care medical visits. Educational interventions did not significantly affect IOP values. Patients who are not adherent tend to have low visual acuity.